Sexual Education for Children with Special Needs through Learning Media based on Universal Design for Learning - Maslahah, Sayidatul; Prasadana, Muhammad Anggie Farizqi; Kamila, Aisyah Nur; Septiandi, Muhammad (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Sexual education is very important to be taught to young children, especially children with special needs. Sexual violence can intentionally occur to someone in a sexual manner. This can even extend to attempted rape, sadism in sexual relationships, other unwanted sexual activities, demeaning and hurting or injuring the victim. One effort to prevent sexual violence is to equip young children with knowledge, skills, and abilities to protect themselves from the threat of sexual violence. The method used is descriptive qualitative research. The subjects in this study are teachers in one Special School. Data collection in this study uses observation, interviews, and documentation techniques. Data analysis techniques use qualitative descriptive analysis techniques. The results of the study show that special teachers need learning media for more structured and systematic inclusive education according to the learning stage process. Until now, there is still minimal learning media used for sexual education, especially for children with special needs. Good learning media must have clear, communicative, concise, and systematic language use. The scope of the content in the learning media must also adjust to the conditions of students who will be given learning.